The paradox of technology innovativeness and risk perceptions – a profile of Asian smartphone users - Wang, Xiaohui (2022)
Risk perceptions and technology innovativeness are the two primary factors related to the adoption of mobile technologies. The current study examines the role of technology innovativeness and risk perceptions on smartphone use and dependence in an Asian context. A total of 9086 participants were recruited through online surveys from ten Asian countries. Ordinary least squares regression analyses revealed the effects of technology innovativeness, information security, privacy concern, and their interactions on smartphone use and dependence. Moreover, based on users’ smartphone usage patterns and perceptions, this paper identified four homogeneous groups using cluster analysis. Results shows that Asian smartphone users can be segmented into four groups: innovators, conservatives, moderators, and laggards. The four clusters show significant differences in demographic features. Theoretical and practical implications are discussed based on these findings.